Effects of forest management on epiphytic lichen diversity in Mediterranean forests - Aragón, Gregorio; Martinez, I.; Izquierdo, P.; Belinchon, R.; Escudero, A. (APPLIED VEGETATION SCIENCE, 2010)
Question What are the responses of epiphytic lichens to the intensity of management along a large environmental gradient in Mediterranean Quercus forests? Location Central Spain. Methods This study was carried out on 4590 trees located in 306 forest stands dominated by Quercus faginea or Quercus ilex ssp. ballota. The effect of forest management and other predictor variables on several species diversity indicators were studied. Variables modelled were total species richness, cyanolichen richness and community composition. A large number of predictor variables were included: forest fragmentation (patch size, stand variability), climate and topographic (altitude, slope, sun radiation, annual rainfall and mean annual temperature) and intensity of management. General linear models and constrained ordination techniques were used to model community traits and species composition, respectively. Results Total richness and especially cyanolichens richness were significantly and negatively affected by the intensity of management. Lichen composition was influenced by management intensity, climatic and topographic variables and stand variability. Conclusions In Mediterranean forests, human activities related to forestry, agricultural and livestock use cause impoverishment of lichen communities, including the local disappearance of the most demanding species. The conservation of unmanaged forests with a dense canopy is crucial for lichen diversity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: Community traits; Cyanolichens; Drivers of composition; fragmentation; land use; oak forests; Spain; Variation partitioning

Effects of the holm-oak canopy on the distribution of terricolous bryophytes and lichens - Casas-Garcia, S.; Burgaz, A. R.; Escudero, A. (CRYPTOGAMIE MYCOLOGIE, 2005)
The effects of holm-oak canopy (Quercus ilex ssp. ballota) onterricolous bryophytes and lichen were studied in the central part of the Spanish Mediterranean region. Three habitats were distinguised: understorey, crown border and open grassland. In all cases, the understorey is floristically poor compared with open grassland. In the N-exposed stands species richness is more homogenous between canopy border and open grassland, while in-S exposed ones differences among habitats are more pronounced. Cladonia rangiformis, C foliacea, C cervicornis and Cetraria aculeata have higher presence and cover values in all situations, and the bryophytes Hypnum cupressiforme and Pleurochaete squarrosa are the main species. Most of the acrocarpic mosses and fruticose lichens grow on the canopy border or open grassland, while pleurocarpic mosses and foliose lichen with cyanobacteria are most frequent under N-exposed canopies. The holm-oak crown causes variations in insolation, rain distribution, temperature and wind, and strongly influences the distribution of lichens and bryophytes.
The following values have no corresponding Zotero field: pub-location: 12 RUE DE BUFFON, 75005 PARIS, FRANCE publisher: ADAC-CRYPTOGAMIE
Keywords: bryophytes; lichens; terricolous; canonical ordina

Nitrogen-use efficiency: trade-offs between N productivity and mean residence time at organ, plant and population levels - SILLA, F.; Escudero, A. (Functional Ecology, 2004)
* 1Nitrogen-use efficiency (NUEN) is often decomposed into the product of N productivity (AN) and the mean residence time of N (MRTN). Theory suggests a trade-off between both components, but direct experimental evidence is still scarce. A field study with young trees of the evergreen Quercus ilex and the marcescent-evergreen Quercus faginea was carried out to test this trade-off through analysis of plant traits at organ, whole-plant and population levels. * 2Specific leaf area (SLA) was the main trait positively related to AN in Q. faginea. By contrast, greater litter production and consumption by caterpillars resulted in larger N losses and shorter MRTN in Q. faginea. Early leaf senescence in Q. faginea produced leaf litter with high N concentration that contributed significantly to N loss. Moreover, Q. ilex had higher plant survivorship. The inverse relationship between leaf longevity and SLA is probably a key component of the trade-off between N losses and plant N productivity. * 3Quercus faginea had greater N uptake from soil, linked to its longer specific root length of fine roots and greater biomass allocation to underground tissues. Smaller N losses in Q. ilex compensated for its smaller N uptake and allowed a similar N balance at whole-plant level. * 4Our results support the hypothesis of a trade-off between AN and MRTN. Quercus ilex had a long MRTN, while Q. faginea has a high AN, and vice versa. The long MRTN in Q. ilex involves not only reduced N loss through long intrinsic leaf life span, but also resistance to harsh environmental factors and defence against herbivores. This suggests that a long MRTN is a potentially successful strategy in nutrient-poor environments.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Drought stress; herbivory; nitrogen loss; nitrogen uptake; plant strategies

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, A.; Mediavilla, S. (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp

Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species - Mediavilla, S.; Escudero, A. (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Leaf growth; leaf life span; mean residence time; nitrogen; phosphorus